Contribution of Soil Microorganisms in Upkeeping Soil Health - Kundu, Manik Chandra (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
Soil is a finite and non-renewable natural resource and is a beautiful gift of nature to humankind. However, soil health deterioration is a great concern for human, animal, and plant health today. Air, groundwater, and surface water consumed by humans can be polluted by mismanaged and contaminated soil. Adverse impacts of intensive agriculture include loss of biodiversity, nitrogen discharges into surface and groundwater, eutrophication of surface water, contamination of groundwater from pesticides and nitrate, and ammonia volatilization due to indiscriminate use of manure and fertilizers. Therefore, soil protection is a high priority, and a thorough understanding of ecosystem processes is critical in ensuring that soil remains healthy. Soil health is defined as the continued capacity of soil to function as a vital living system within the ecosystem and land-use boundaries to sustain biological productivity, promote the quality of air and water environments, and maintain plant, animal, and human health. The biological components consisting mainly of soil microorganisms can make up only a very small fraction of topsoil volume. However, soil microorganisms play a major role in nutrient (N, P, S) cycling and decomposition of organic matter. Thus, healthy soil can be identified by measuring soil microbial population dynamics. The changes in microbial populations and their activities in various soil conditions are excellent indicators of change in soil health. The bioavailability of chemicals is also an essential issue for soil health. The impact of such substances on soil health is dependent on microbial activities. This paper will discuss the role of soil microorganisms in maintaining and sustaining soil health in this paper.